São Paulo é uma escola: uma política curricular sob o olhar dos educadores - Cocco, Cecília Aparecida (2012)
This doctoral thesis analyzes in loco the reach of public policy destined for the Basic Education of the municipal network of teaching in Sao Paulo s city council, the Municipal Secretary of Education, utilizing São Paulo is a School, from the period of 2005 to 2008, as a banner, and looks at its repercussions in teaching practice. Part of the hypothesis, that the proposal centralized financial resources, did not yield continuity to the previous policies and interrupted an intersecretarial and intersectorial work experience that occurred in the Subcouncil of Vila Prudente/Sapopemba, in the periphery of the eastern zone of the city. With the objective of showing how a public policy posterior in the period of 2001-2004 had a strong impact in the organization of school and curriculum, it destructured teaching teams and altered the composition of forces in schools. Adhering to qualitative methodology, the research reunited teachers of the Basic Education, representatives of the scholastic unities located in the Subcouncil of Vila Prudente/Sapopemba, belonging to two regional directories of teaching and participants of the acts, to evaluate the impact on school life. As a methodological instrument, it supported itself on group discussion, in which the actors, put in debate, extract, as a collective subject, the common evaluative position in turn of this public policy, administrative and curricular, transcribed in text and registered in DVD, attached to the text of this thesis. The research reveals that, without the effective participation of the educators as protagonists of the reforms, the proposals that jettison the teachers are demobilizers and have little possibilities of elevating the quality of education